2011
DOI: 10.1162/rest_a_00060
|View full text |Cite
|
Sign up to set email alerts
|

Do Small Businesses Create More Jobs? New Evidence for the United States from the National Establishment Time Series

Abstract: We use the National Establishment Time Series (NETS) to revisit the debate about the role of small businesses in job creation (Birch, 1987; Davis, Haltiwanger, & Schuh, 1996a). Using the NETS data, we examine evidence for the overall economy, as well as for different sectors. The results indicate that small firms and small establishments create more jobs, on net, although the difference is much smaller than Birch's methods suggest. Moreover, in the recent period we study, a negative relationship between establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
224
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(253 citation statements)
references
References 32 publications
15
224
0
3
Order By: Relevance
“…According to the well-known standard economic theory by Jovanovic (1982), younger firms create more demand for employment. In line with this finding, some relevant studies have empirically demonstrated what this theory states (Earle and Telegdy 2011;Neumark et al 2011;Haltiwanger et al 2013;Lawless 2014). However, this does not hold for firms older than 5 years, and it is worth noting that some studies have presented a contrary result (Huber et al 2012).…”
Section: Smes' Basic Factors and Job Creationsupporting
confidence: 57%
“…According to the well-known standard economic theory by Jovanovic (1982), younger firms create more demand for employment. In line with this finding, some relevant studies have empirically demonstrated what this theory states (Earle and Telegdy 2011;Neumark et al 2011;Haltiwanger et al 2013;Lawless 2014). However, this does not hold for firms older than 5 years, and it is worth noting that some studies have presented a contrary result (Huber et al 2012).…”
Section: Smes' Basic Factors and Job Creationsupporting
confidence: 57%
“…7 We use the distinction of the U.S. Census Bureau, according to which nonemployers are business units without paid employees. For firm-level analysis of employment dynamics including both employer and nonemployer firms see Davis et al (2009);Neumark et al (2011), whether Haltiwanger et al (2013) use only employer firms. Notice that we use here the same set of export data as those employed in Bernard et al (2015).…”
Section: Datamentioning
confidence: 99%
“…Small firms, however, also differ from large ones in a number of other ways. For instance, in comparison to large and old firms small businesses and new entrants are more likely to experience job losses (see, e.g., Bartelsman et al 2005, Voulgaris et al 2005, and Neumark et al 2011). This suggests a considerable volatility in the number of employees in small firms usually referred to as churning.…”
Section: Introductionmentioning
confidence: 99%